The Position of Living Law as a Legal Institution in Law No. 1 of 2023 on the Criminal Code - Redy, Simon Albertian (Journal of Law, Politic and Humanities, 2025)
This study aims to determine and analyze the basis for consideration of living law as part of Law No. 1 of 2023 concerning the Criminal Code.  To know and analyze the forms of living law that will be applied in Law no.1 of 2023 concerning the Criminal Code. To know and analyze the implementation of living law rules in Law No. 1 of 2023. This research uses normative legal research with a statutory approach in conducting dissection as the object of research. The results show that Law No. 1 of 2023 on the Criminal Code (KUHP) confirms the recognition of customary law or living law as an integral part of the national legal system, as mandated by the 1945 Constitution. This recognition aims to provide protection to the community, including indigenous peoples, by strengthening the laws that live in the community through updates and adjustments to the new Criminal Code. Previously, the colonial influence on the old Criminal Code did not adequately accommodate customary law. In its implementation, living law is reflected in Article 2 paragraph (2), which regulates forms of customary punishment such as non-material compensation, performance of customary rituals, apology as a cover of shame, and exile of the perpetrator from the community. These forms are local in nature and adapt to the local culture. The implementation of the new Criminal Code is based on three main foundations, namely philosophical, sociological, and juridical, which ensure the application of customary law in accordance with the social context and national legal norms.